EFFECT OF USEOF KATUK LEAF EXTRACT, LEMURU FISH OIL AND VITAMIN E TO PERFORMANCE AND QUALITY OF BROILER CHICKENS - Basyaruddin Zain (Jurnal Agroindustri, 2012)
This research was conducted to determine the effect of leaf extract katuk (EDK), lemurufish oil (MIL) and vitamin E as a substitute for a commercial feed supplement on performance and quality of broiler chickens. The total of 195 birds were used as objects in this study.  Design research used Completely Randomized Design (CRD) with 13 treatments and 3 replications. Each test consisted of five broiler chickens. The data obtained were analyzed according to the design used and Test DMRT (Duncan Multiple Range Test) to examine differences in treatment effect. The results showed that the use katuk leaf extract, lemuru oil, and vitamin E  did not differ significantly (P>0.05) on ration consumption, weight gain, feed conversion and internal organ weight of broiler chickens.  In contrast, there were highly significant differences (P<0.01) on serum, cholesterol level, triglyceride, LDL cholesterol and HDL cholesterol.  Similarly, feeding sauropus androgynus extract and lemuru fish oil plus vitamin E are highly significantly (P <0.01) affected weat cholesterol, fant and protein.